LEGAL PROTECTION AGAINST GENDER DISCRIMINATION IN TERMINATION OF EMPLOYEE EMPLOYMENT DUE TO PREGNANCY OUT OF WEDDING - Sabina, Sabina Amelia Sopian (Journal Social Sciences and Humanioran Review, 2024)
This study investigates how the Indonesian Manpower Law can protect female workers from gender discrimination related to pregnancy, especially premarital pregnancy. Law No. 13 of 2003 on Manpower provides protection for female workers, but the culture of discrimination still often occurs. The normative legal method using laws and regulations in this study to investigate relevant regulations and their implementation in practice. The study shows that female workers who are laid off due to premarital pregnancy have the right to seek justice. However, many working women are not aware of their rights, and regulations are still weak. Therefore, workers' rights must be protected through stricter supervision, better legal protection, and ease of reporting violations.